2004
DOI: 10.2170/jjphysiol.54.431
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Modules in the Cerebellum

Abstract: ings must be evaluated with caution because the possible spread of stimulating currents to outside the cerebellum was not accurately controlled at that time.During the past four to five decades, research on the cerebellum has advanced markedly and our knowledge about its functional involvements and neuronal mechanisms has been conspicuously improved [6][7][8][9][10]. A new concept regarding the cerebellum has thus developed. The cerebellum has a unique modular structure, including a cortical microzone, a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 110 publications
(82 reference statements)
0
38
0
2
Order By: Relevance
“…In addition to its role in motor control, the cerebellum is also involved in autonomic nervous function, and several studies have demonstrated that some modules within the cerebellum are dedicated to cardiovascular function and exert influence on the brainstem cardiovascular centers. 21, 22 For example, anatomic evidence supports the involvement of fastigial nucleus neurons and the medial portion of the cerebellar vermis in cardiovascular function. 23, 24 In the present study, areas of the cerebellar vermis showing increased rCBF corresponded to the medial portion of the vermis, including the fastigial nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in motor control, the cerebellum is also involved in autonomic nervous function, and several studies have demonstrated that some modules within the cerebellum are dedicated to cardiovascular function and exert influence on the brainstem cardiovascular centers. 21, 22 For example, anatomic evidence supports the involvement of fastigial nucleus neurons and the medial portion of the cerebellar vermis in cardiovascular function. 23, 24 In the present study, areas of the cerebellar vermis showing increased rCBF corresponded to the medial portion of the vermis, including the fastigial nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the medial cerebellum, particularly vermal lobules VI–VII, has been shown to participate in heart rate conditioning and the conditioned bradycardic response [55, 57, 58, 9698]. The fastigial nucleus may also be involved in autonomic cardiovascular modulation as part of the baroreceptor reflex, and vermal stimulation may lead to changes in arterial blood pressure, heart rate, and regional blood flow [42, 54, 56, 59]. Our observations thus elaborate upon these earlier findings and provide experimental evidence in humans in favor of a role for the posterior cerebellar vermis in nonsomatic cardiovascular regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is accumulating evidence regarding cerebellar involvement in feeding [4351], thirst [52, 53], cardiovascular regulation [5459], sexual function [6065], fear conditioning [6672], and nociception [7376]. These reports suggest a functional relationship between the cerebellum and the hypothalamus in the control of autonomic states relevant to emotional expression.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of impaired responsiveness of arterial blood pressure to aversive stimuli in animals [87] and a less extensive increase in heart rate during fear conditioning tasks in subjects with vermal lesions [75] indicate that the cerebellum is also involved in the autonomic neural pathways that subserve the cardiovascular system in emotion regulation [87][88][89]. Furthermore, fMRI studies have implicated that the cerebellar vermis is involved in autonomic responses that are associated with fear conditioning [78][79][80]83].…”
Section: Cerebellar Involvement In the Unconscious Component Of Emotionsmentioning
confidence: 99%